The Examination On The Industry 4.0 Of The Dispositional Affect In Accountant’s Ethic Lapses Behavior - Alfonsa Dian Sumarna (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2020)
Finance and accounting are an area that are many unethical activities could be happen especially in this fourth industrial revolution today. In this study, we analyze the impact among the dispositional affect (positive affect and negative affect), gender, age, educational background, work experience to ethical lapses behavior. Dispositional affect is divided into four states which are the enthusiastic, the happiness, the frustration, and the fear. We find that disspositional affect, age, education background, work experience and gender are not significantly influences the ethical lapses behavior. Enthusiastic and happy people will try to avoid doing ethical lapses even from their superior’s behest because they have genuinely positive achieve goals and nobel expectations into their job. Negative affect of frustration and fear also have no significant influence to the ethical lapses behavior. The ambiguity of situations that tend to be uncertain and unpredictable can cause anxiety in other psychological cases. The frustation and fear make people tend to aware and protect themselves from bad consequence of ethical lapses. Other than variable educational background, age, work experience, negative affect of frustrated and negative affect of fear have highly significant correlation. The implications from this study for practice and research are also provided.